Exploring Quantum Dynamics of Dissipative Systems in Living Organisms - Orzhelskyi, Igor; Kuznetsov, Andrey; Dijk, Elena Van (Advanced Research in Biological Science Vol. 9, 2024)
The functional information of dissipative systems in Living Matter correlates with both the physical and mathematical regularities defining its material and quantum operational levels. The quantum operational level of Living Matter necessitates employing mathematical models to describe spaces of high dimensions. The physical significance of such an approach helps ascertain the meaning of “action information” as the “quantum information” of dissipative systems. Homeostasis is an integrative dynamic process regulating the functional and morphological (morphofunctional) relative internal constancy of a living organism.32 Tissue homeostasis ensures the preservation of the relative stability of the total number of cells, an optimal ratio between dividing cells, differentiated, and apoptotic (undergoing apoptosis) cells within the tissue composition. The competitive balance between a living organism's metabolism and homeostasis is determined by the quantum characteristics of dissipative systems. The characteristics of "quantum information" in dissipative systems show broad patterns that can be used to analyze the mathematical and physical underpinnings of "quantum computers" and materials created using "quantum dots."